The Effect of Botulinum Toxin- A injection for the Lower Limb in Children with Spastic Cerebral Palsy - Tsegmid, Narantsetseg; Batbold, Galindev; Erdenebileg, Nasantogtokh; Shirmen, Batchimeg; Ganbold, Davaasuren; Zagd, Gerelmaa; Avirmed, Baljinnyam (Central Asian Journal of Medical Sciences, 2023)
Objectives: To investigate the effect of botulinum toxin-A (BoNT-A) on the age groups and gross motor function classification level in children with cerebral palsy (CP). Method: In this study, 116 children with spastic CP were investigated. BoNT-A was injected into the spastic muscles of the lower limbs of all participants. All participants received physiotherapy and functional electrical stimulation for 3 months after injection. We measured the change in spasticity using the Modified Ashworth Scale and gross motor function using the GMFM-88. Spasticity was measured before injection and at 1 and 3 months after injection. Measurement of gross motor function was performed before and after the injections. Results: The effect of BoNT-A injection in combination with physiotherapy and electrical stimulation significantly improved spasticity and gross motor function. After BoNT-A injection, younger children showed reduced spasticity and improved gross motor skills compared to older children. At the gross motor level, sitting, standing, and walking improved in children with gross motor function classification levels I-III, and posture and mobility improved in children with gross motor function classification levels IV-V. Conclusions: We conclude that BoNT-A injection is effective for improving gross motor function in patients younger than 72 months of age.